Non-invasive Diagnostics of Liver Fibrosis - Mihaylov R. (Sciendo, 2017)
Detecting new units of pathogenesis in the liver fibrosis due to alcoholism, chronic viral Hepatitis B and C, non-alcoholic fatty liver disease (NAFLD), autoimmune, parasitic and metabolic diseases and other, reveals perspective for new non-invasive serum biomarkers. In fibrosis, from the wide variety of markers enzymes, proteins and cytokines are mainly used. While direct biomarkers reflect the stage of fibrosis and fibrinogenesis, indirect markers allow assessment of the general liver functions. The combination of direct and indirect markers increases the diagnostic reliability and therefore these panels and indices are investigated quite intensively in recent years in order to decrease the number of liver biopsies without completely replace it, which is still regarded as the reference method.